(untitled) (Revista Innova Educación, 2021)
The objectives of this research were to know the teaching styles, the learning styles of the participants, and how they influence the transmission of knowledge through the use of information pills. A cross-sectional ethnographic design was used in the study. Fourteen groups of students of the primary education teaching degree from the University of Zaragoza participated in the second semester of the 2019 academic year. The instruments used are the questionnaires of learning styles, pedagogical beliefs, and evaluation of the information pill. The results obtained indicate a relationship between pedagogical beliefs, the learning style, and the way of transmitting information, with instruction in these aspects being necessary for both future teachers and those who are active teachers who take into account the skills and abilities of the student can cause significant changes in their learning.